Reliability and day-to-day variability of peak fat oxidation during treadmill ergometry - De Souza Silveira, Raul; Rosenberger, Friederike (Journal of the International Society of Sports Nutrition, 2016)
Exercising at intensities where fat oxidation rates are high has been shown to induce metabolic benefits in recreational and health-oriented sportsmen. The exercise intensity (Fatpeak) eliciting peak fat oxidation rates is therefore of particular interest when aiming to prescribe exercise for the purpose of fat oxidation and related metabolic effects. Although running and walking are feasible and popular among the target population, no reliable protocols are available to assess Fatpeak as well as its actual velocity (VPFO) during treadmill ergometry. Our purpose was therefore, to assess the reliability and day-to-day variability of VPFO and Fatpeak during treadmill ergometry running.
Gesehen am 07.05.2020